2020
DOI: 10.1051/0004-6361/202038557
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous transverse oscillations of a coronal loop and a filament excited by a circular-ribbon flare

Abstract: Aims. The aim of this study is to investigate the excitation of kink oscillations in coronal loops and filaments, by analyzing a C3.4 circular-ribbon flare associated with a blowout jet in active region 12434 on 2015 October 16. Methods. The flare was observed in ultraviolet and extreme-ultraviolet wavelengths by the Atmospheric Imaging Assembly on board the Solar Dynamics Observatory (SDO) spacecraft. The line-of-sight (LOS) magnetograms of the photosphere were observed by the Helioseismic and Magnetic Imager… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…A bundle of magnetic field lines are involved in the reconnection process. For the field lines threading the filament, the jet directly hits the filament to oscillate longitudinally, as indicated by observations (Luna et al 2014;Zhang et al 2017;Zhang 2020) and illustrated by numerical simulations in this paper in 1D or in Luna & Moreno-Insertis (2021) in 2D. For the field lines encircling the filament, the jet plasma does not impact the filament material directly.…”
Section: How Filament Decayless Oscillations Are Maintainedmentioning
confidence: 54%
“…A bundle of magnetic field lines are involved in the reconnection process. For the field lines threading the filament, the jet directly hits the filament to oscillate longitudinally, as indicated by observations (Luna et al 2014;Zhang et al 2017;Zhang 2020) and illustrated by numerical simulations in this paper in 1D or in Luna & Moreno-Insertis (2021) in 2D. For the field lines encircling the filament, the jet plasma does not impact the filament material directly.…”
Section: How Filament Decayless Oscillations Are Maintainedmentioning
confidence: 54%
“…As mentioned in Section 1, CFs are frequently associated with hot coronal jets observed in EUV wavelengths Zhang & Ni 2019;Zhang 2020;Zhang et al 2021) or cool surges observed in Hα (Wang & Liu 2012;Xu et al 2017). In Figure 1, the C4.2 class flare is accompanied by a blowout jet (Zhang et al 2016a; Dai et al 2021).…”
Section: Relation With Coronal Jetsmentioning
confidence: 93%
“…CFs are usually triggered by filament eruptions (Joshi et al 2015;Xu et al 2017;Yang et al 2020a), which may also generate coronal jets (Wang & Liu 2012;Joshi et al 2018;Zhang et al 2016aZhang et al , 2021Zhang & Ni 2019;Zhang 2020;Dai et al 2021) or drive coronal mass ejections (CMEs; Sun et al 2013;Joshi et al 2015Joshi et al , 2017Liu et al 2019Liu et al , 2020. CFs show similar dynamics to that of two-ribbon flares.…”
Section: Introductionmentioning
confidence: 99%
“…Phase mixing with anomalously high viscosity is also important in the dissipation of energy during loop oscillations (Ofman & Aschwanden 2002). Small-amplitude, transverse oscillations of coronal loops without significant damping have been noticed (Anfinogentov et al 2013;Nisticò et al 2013;Li et al 2018a;Zhang 2020). The observed loop oscillations in combination with magnetohydrodynamics (MHD) A&A proofs: manuscript no.…”
Section: Introductionmentioning
confidence: 98%